Knowledge of Cardiopulmonary Resuscitation among Student Nurses in Aliko Dangote College of Nursing Science Bauchi - Maimuna, Muhammad; Musa, Muhammad Maryam; Salisu, Umar Muhammad; Dambam, Muhammad Fatima (THRIVE Health Science Journal, 2026)
Cardiopulmonary Resuscitation (CPR) is a critical life-saving intervention required to sustain circulation and oxygenation during cardiac arrest, especially within clinical and community settings where nurses often serve as first responders. Ensuring adequate CPR knowledge and competence among student nurses is therefore an essential component of nursing education and professional preparedness. This study assessed the level of knowledge, practice, and factors influencing CPR competency among student nurses in Aliko Dangote College of Nursing Sciences, Bauchi State. A descriptive cross-sectional survey design was adopted, and a stratified random sampling technique was employed to select 171 respondents from a target population of 597 students. Data were collected using a structured, validated, and reliable questionnaire, and analyzed using simple frequency distribution and percentages. Findings revealed that more than half of the respondents demonstrated good knowledge of CPR, including awareness of the recommended CAB sequence, appropriate depth of chest compressions, and use of an Automated External Defibrillator (AED). The study also showed that over 55% of student nurses possessed satisfactory CPR practice skills, such as correct hand placement, adherence to the 30:2 compression-to-ventilation ratio, and understanding the importance of full chest recoil. However, gaps were identified in areas such as advanced steps of CPR, sustained practical competence, and consistent exposure to hands-on training. The study further identified several factors influencing CPR practice, including inadequate simulation resources, limited access to trained instructors, and insufficient practical opportunities. Respondents strongly agreed that CPR competence can be improved through simulation-based learning, peer-led training, digital media support, and incentive-based motivation. The study concludes that while CPR knowledge among student nurses is generally high, practical proficiency requires further strengthening. It recommends enhanced training programs, provision of adequate learning resources, regular refresher sessions, and improved supervision to bridge the knowledge–practice gap and improve overall CPR competence among nursing students.